The Formation of Pitted Features on the International Simple Glass during Dynamic Experiments at Alkaline pH. (11th January 2019) - Fisher, Adam J.; Hyatt, Neil C.; Hand, Russell J.; Corkhill, Claire L.
ABSTRACT: The forward rate of dissolution of the International Simple Glass (ISG) was determined under alkaline conditions at 40 ° C using the Single Pass Flow Through (SPFT) method. Forward rates were consistent with those obtained in the literature for this glass composition. The formation of altered gel layers and surface pits was observed on the surface of glass particles, especially at the very highest pH values, despite the application of high flow rates to prevent the build-up of solubility limiting phases. These features could be attributed to preferential localized dissolution at sites with a higher alkali concentration or from a separate, less durable, vitreous phase. These results may indicate that surface pit and altered gel formation occurs under the forward rate of dissolution as imposed by the SPFT method, particularly for simplified borosilicate glass materials.